Total segmental aplasia of uterus body in bitch - Leonardo Martins Leal; Fábio Rodrigo Castro Bastos; Tais Harumi de Castro Sasahara; Paola Castro Moraes; Márcia Rita Fernandes Machado (Asian Pacific Journal of Reproduction, 2019)
Congenital anomalies of the female tubular genital tract are rare and known as segmental aplasia, resulting from incomplete development of paramesonephric ducts during embryonic stage, which originate from the cranial portion of vagina, cervix, uterus and oviducts. In the literature consulted, several reports of uterine horn aplasia are described in bitches, however there is only one report described in the world literature on total aplasia of the body of the uterus. This study aimed to describe the case of a two years old bitch, no breed defined, with 12 kg of weight, with segmental aplasia of uterus body diagnosed during ovariohysterectomy. During surgery it was noted that the bitch had the ovaries and uterine horns in their anatomical position, however an aplasia was noted in the body of the uterus. It was also found that the uterine horns had liquid inside, suggesting hydrometra. It was concluded in this case that although segmental aplasia of the body of the uterus is rare and difficult to diagnose by maintaining normal cyclicity of the female, it should be considered in dogs that do not have bloody vaginal discharge in proestrus and can not become pregnant after natural coverage or artificial insemination.